Implementation of Akhlaqul Karimah Through Islamic Religious Education Approach In Early Children - Imam Tabroni; Sania Rahmania (East Asian Journal of Multidisciplinary Research, 2022)
Akhlak are the concern of people everywhere, both in advanced societies and underdeveloped societies, because if in a society there are many people whose Akhlak have been damaged, the society will be damaged. This shows that the position of morality in human life occupies a very important position, both as individuals and as members of society and the nation. "The rise and fall of a nation depends on the moral state of the nation itself. If their Akhlak are good, they will prosper both physically and mentally, but on the contrary if their Akhlak are bad, the nation will be damaged. In the hadith of the Prophet Muhammad SAW. which means “Educate your children because they were born to live in an age different from yours”. Because children are a gift or a mandate from Allah SWT. which must always be maintained and maintained continuity.